KUMBANG KOKSI SEBAGAI IDE MEJA KOPI - Muhammad Jauhar Ansori; Dwi Susila (Universitas Islam Nahdlatul Ulama Jepara, 2020)
Furniture is a tool that is needed, useful, or liked, such as items or objects that can be moved around, used to equip homes, offices and so on. To make a furniture product must start with the correct stages, namely from the researching, planning, inventing and constructing processes. A mature design is very synergized in determining the final result. If the design is ripe, the results obtained will be satisfactory and will not experience errors. In making the design the writer takes the concept of the koksi beetle shape. The koksi beetle chosen comes from the Coleotera Order family because it has interesting shapes and colors. The koksi beetle is suitable to be applied as a concept for furniture products in the form of a simple coffee table set, with a flexible stool which can be made individually or into a complete unit with an additional table. In order to match the theme of the coffee table, the leaves are in the form of leaves and the stool is in the shape of a koksi beetle. In the process of making the product, it begins with making several sketches and then selected based on the shape according to the desired concept.